DISCOVERY OF THE END-EARLY PALEOZOIC ADAKITE IN THE BUQINGSHAN AREA, QINGHAI PROVINCE, AND ITS TECTONIC IMPLICATIONS - Bian Q.T.; Chang C.F.; Li J.L.; Pospelov I.I.; Li H.M. (My University, 2007)
The adakite was recently revealed in the Buqingshan ophiolite complex, a western sector of the A'nyemaqen ophiolite belt in the northern part of the Qinghai-Tibet Plateau. The adakite consists of granodiorite-tonalite intruded in the Early Paleozoic ophiolite complex. The mineralogical phases pserent in the adakite are mainly plagioclase, quartz, hornblende, biotite, rare pyroxene and potassium feldspar; and accessory phases are apatite, zircon, sphene and magnetite etc. The adakite is calc-alkaline, and characterized by high SiO2 (63.65%-71.59%), high Al2O3 (14.81%-16.11%), high Na2O (4.68%-5.33%) and Na2O/K2O (1.48-3.08, av. 2.39) ratios, high Sr(444.08 × 10-6-560.41 × 10-6) and Sr/Y (50.8-105.3), rich in large ion lithophile elements (LILE), depleted in high strength field elements (HFSE), weakly negative Eu anomalies, strong depletion of heavy rare earth elements (e.g., Yb = 0.38 × 10-6-0.74 × 10-6) and Y (4.93 × 10-6-11.03 × 10-6), high La/Yb(44.93-90.97), positive Ba and Pb but negative Nb and P anomalies. These geochemical characteristics suggest that the Buqingshan adakite belongs to typical adakite (O-type, HSA). A TIMS zircon U-Pb age of 402 ± 24Ma for the adakite have been obtained. The Buqingshan adakite was most probably derived by the partial melting of the subducting Kunlun-Qilian-Qinling oceanic crust (basaltic oceanic crust plus its overlying sediment) at garnet amphibolite-facies condition. The discovery suggests that the part of the Kunlun-Qilian-Qinling oceanic crust of the study area was subducted northward, and the subduction zone was situated to the south of the A'nyemaqen ophiolite belt in the end-Early Paleozoic period. It is also of implication that porphyry-type and hydrothermal-type Au, Ag, Cu, Mo mineralization related with typical adakite probably existed in the A'nyemaqen ophiolite belt.
Keywords: A'NYEMAQEN OPHIOLITE BELT; ADAKITE; END-EARLY PALEOZOIC; GEOCHEMISTRY; TIBETAN PLATEAU; Paleozoic; Paleozoic::Devonian::Lower::Emsian; Палеозой::Девонская::Нижний::Эмсский